Length of stay and hospital readmission for persons with disabilities. - Ottenbacher, K J (2000)
OBJECTIVES: Length of stay (LOS) and hospital readmission for persons receiving medical rehabilitation were examined. METHODS: A total of 96,473 patient records (1994-1998) were analyzed. Mean age of patients was 68.97 years; 61% were female and 83% were non-Hispanic White. RESULTS: A decrease in LOS of 6.07 days (SD = 3.23) and increase in hospital readmission were found across all impairment groups (P < .001). Readmission increases ranged from 6.7% for amputations to 1.4% for orthopedic conditions. LOS was longer (2.1 days) for readmitted patients (P < .01). Age was not a significant predictor of rehospitalization. CONCLUSIONS: Understanding variables associated with rehospitalization is important as prospective payment systems are introduced for postacute care.